TALKING CHIPS: MODEL PEMBELAJARAN COORPERATIVE DAPAT MENINGKATKAN HASIL BELAJAR SISWA UNTUK SEMUA - Abdul Manaf (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
Lack of questions and answers and group discussions built by the teacher in conducting learning in the classroom so that students are less effective and students cannot learn actively. The ability and responsibility of teachers in choosing learning methods or models that are suitable and in accordance with teaching material in a learning process determine the continuity of learning, teachers still use conventional learning models that make students passive in class. Therefore, students' communication skills are very low which causes student learning outcomes to be based on an average. Thus the cooperative learning model Talking Chips type is needed which applies to be adapted to teaching materials in order to improve students' abilities in communication, and can improve student learning outcomes